Effect of Family Income, Education, Occupation, and Birth Weight on Child Growth at Aisyiyah III Kindergarten, in Kadipiro, Indonesia - Haryanti, Rusiana Sri; Murti, Bhisma; Poncorini, Eti (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2016)
Background: Children under five years old are the future generation. Stages of child development during the golden period require stimulation to increase the potential of healthy children. As such the growth and development of children under five need serious attention. This study aimed to analyze the effect of family income, education, maternal occupation, and birth weight, on the development of children under five.Subjects and Method: The study was observational analytic using cross sectional design. The study was conducted in Kindergarten of Aisyiyah III Kadipiro in May-June 2016. A total sample of 50 subjects was selected for this study. The independent variables were family income, education, maternal occupation, and birth weight. The dependent variable was child development. The data were analyzed using a multivariate linear regression model.Results: Family income had a negative relationship with child development, but was not statistically significant (OR= 0:13; 95% CI <0.01 to 5.02; p= 0.274). Maternal education (OR= 22.22; 95% CI= 1.35 to 365.07; p= 0.030), occupation (OR= 96.18; 95% CI= 1.69 to 5644.84; p=0.027), and birth weight (OR= 32.21; 95% CI= 1.76 to 588.84; p= 0.019), had positive and statistically significant relationship with child development.Conclusion: Maternal education, maternal occupation, and birth weight have positive effect on child development.Keywords: family income, education, occupation, birth weightCorrespondence:Rusiana Sri Haryanti. School of Health, STIKes PKU Muhammadiyah, Surakarta, Indonesia. Email: rusianamolyn@gmail.com.Journal of Maternal and Child Health (2016), 1 (1): 1-6https://doi.org/10.26911/thejmch.2016.01.01.01